Edukasi Penanganan Pernikahan Usia Dini, Stunting dan Pendidikan Melalui Organisasi Nasyiatul Aisyiyah Desa Windurejo, Mojokerto - Yelvi Levani; Nurhidayatullah Romadhon; Moch. Syakroni; Amanat Solikah; Yusuf Nurmansyah (Indonesian Journal Publisher, 2025)
Early marriage can increase the risk of stunting in children, as physically and mentally unprepared mothers are often unable to provide adequate nutrition over a long period of time. This results in impaired growth in children, resulting in shorter height than their age standard. Therefore, the importance of education for adolescents is crucial to delay early marriage and ensure optimal health and development for future generations. The purpose of this community service activity is to develop women's insights and skills so that they have critical awareness, solidarity, care, skills, and are committed to becoming actors of social change to avoid household problems. The stages of implementing activities in Windurejo Village are organized systematically consisting of planning, implementation, and follow-up reporting. The results of the activity showed an increase in participants' knowledge about the dangers of early marriage, the risk of stunting, and the importance of education as a solution. The increase in knowledge was measured through pre-test and post-test which showed an average increase in scores of 30%. Indicators of the success of the activity include the participants' increased understanding of the material presented, active involvement in discussions, and their ability to develop an action plan that reflects their commitment to social change.